2015
DOI: 10.1155/2015/192724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moxifloxacin on Hepatic Redox Status and Plasma Biomarkers of Hepatotoxicity and Nephrotoxicity in Rat

Abstract: Moxifloxacin is a broad spectrum fluoroquinolone antibacterial agent. We examined the hepatic redox status and plasma biomarkers of nephrotoxicity and hepatotoxicity in rat following administration of moxifloxacin (MXF). Twenty-four Wistar rats, 180–200 g, were randomized into four groups (I–IV). Animals in group I (control) received 1 mL of distilled water, while animals in groups II, III, and IV received 1 mL each of MXF equivalent to 4 mg/kg b.w., 8 mg/kg b.w., and 16 mg/kg b.w., respectively. After seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Plasma alkaline phosphatase is one of the liver biomarker enzymes, whose evaluation provides details of pathological damage to the tissue (Mu'azu et al, 2020). A high level of plasma ALP activity has been linked with hepatobiliary dysfunction which is likely a result of hepatobiliary injury and cholestasis (Ore and Olayinka, 2015). The nonsignificant value of ALP activities observed in this study implied that the doses of the extract considered may not affect the hepatobiliary function of the liver.…”
Section: Biochemical Parametersmentioning
confidence: 64%
“…Plasma alkaline phosphatase is one of the liver biomarker enzymes, whose evaluation provides details of pathological damage to the tissue (Mu'azu et al, 2020). A high level of plasma ALP activity has been linked with hepatobiliary dysfunction which is likely a result of hepatobiliary injury and cholestasis (Ore and Olayinka, 2015). The nonsignificant value of ALP activities observed in this study implied that the doses of the extract considered may not affect the hepatobiliary function of the liver.…”
Section: Biochemical Parametersmentioning
confidence: 64%
“…It was hypothesized that VED stimulated the β-oxidation of fatty acids since there was an elevation in the concentrations of acetone. In addition, the level of lipid peroxidation and lipid peroxidation byproducts that are generated is directly proportional to the amount of unsaturated fats [ 51 ]. The results of the present study confirmed this, with higher serum concentrations of unsaturated lipids (L7, L8, L9) and MDA in VED cows.…”
Section: Discussionmentioning
confidence: 99%
“…The GSH level in the liver is a measure of non-enzymatic anti-oxidant and cellular Redox Status of the cells [22] The observed reduction in GSH levels are in accordance with the previously recorded data by many fluoroquinolones [23] . Also, quinolones have the capacity to produce free radicals and change the activity of antioxidant enzymes [24].Moreover, [25] said that, gatifloxacin significantly decreased the activity of superoxide dismutase and blood glutathione levels of treated rabbits. In addition [26].…”
Section: Discussionmentioning
confidence: 99%